Hypertensive disorders of pregnancy increase the risk for chronic kidney disease: A population-based retrospective study - Maika Oishi; Kaori Iino; Kanji Tanaka; Kana Ishihara; Yoshihito Yokoyama; Ippei Takahashi; Hideki Mizunuma (Clinical and Experimental Hypertension, 2017)
Hypertensive disorders of pregnancy (HDP) and chronic kidney disease (CKD) are well-known risk factors for cardiovascular disease (CVD) in later life. However, few studies have investigated the association of HDP with CKD. Moreover, these studies utilized either registry- or clinical-based data and did not include subclinical CKD patients. To address this gap in the literature, we investigated whether HDP is related to CKD, diagnosed based on the estimated glomerular filtration rate (eGFR), in later life. We designed a population-based, retrospective study, and reviewed the results of blood and physiological examinations as well as the results of pregnancy data available in patients’ Maternity Health Record Books for 312 women. We identified 15 women with a diagnosis of CKD based on the eGFR, and 14 women with HDP. We found that women who experienced HDP had a high risk of CKD in later life compared with women without HDP (odds ratio (OR): 4.854; 95% confidence interval (CI): 1.042–22.621). Compared with normotensive women, those who were hypertensive at the time of the examination were significantly associated with CKD (OR: 3.109; 95% CI: 1.213–11.510). Awareness regarding the risk for CKD and CVD in a relatively young age can enable women to prevent diseases effectively.